BOOK REVIEW: VASILE MUSCĂ, “ILUMINISM ȘI ISTORISM [ENLIGHTENMENT AND HISTORICISM]”. CLUJ-NAPOCA: GRINTA, 2008, 191 P. - Amelia PRECUP (Studia Universitatis Babeş-Bolyai. Philologia, 2019)
“What is the Enlightenment?” is one of the most significant questions ever asked, a question that, in many ways, has shaped the world we live in. Either blaming or celebrating the movement, the answers to this question have attempted to contribute to the understanding of the modern world for more than two centuries now. The question started to infiltrate the European political and philosophical thought in the seventeenth century, although it received full articulation only in the late eighteenth century, when it engendered a spirited discussion about what had already been perceived as a decisive shift in Europe’s sense of itself.